New species of Pseudonereis Kinberg, 1865 (Polychaeta: Nereididae) from the Atlantic Ocean, and a review of paragnath morphology and methodology - Conde-Vela, Víctor M. (Zootaxa, 2018)
Pseudonereis gallapagensis Kinberg, 1865 and P. variegata (Grube & Kröyer in Grube, 1858) are the only two species of this genus commonly recorded along Atlantic American coasts, but their type localities are in the Eastern Pacific, and their morphology differs. Two new Pseudonereis species are described from Eastern Mexico: P. brunnea sp. n. from the Gulf of Mexico, and P. citrina sp. n. from the Caribbean Sea, previously confused with P. gallapagensis. In order to facilitate comparisons, descriptions based on specimens from near the type locality for P. gallapagensis (Peru and Ecuador), and topotypes for P. variegata (Valparaiso, Chile), are included. Based on these comparisons and current descriptions, the synonymies of Nereis ferox Hansen, 1882 described from Brazil with P. variegata, and of Pseudonereis formosa Kinberg, 1865 described from Hawaii with P. gallapagensis, are rejected. Consequently, both are regarded as distinct species and revised diagnoses are provided for them. The record of P. ferox from the Gulf of Guinea proved to be an undescribed species, and is herein described as P. fauveli sp. n. The number of paragnath rows in nereidid pharynx areas VII–VIII has been interpreted in several ways, leading to confusion; an alternative method to determine the number of bands and rows is proposed. The midventral region, the division of areas VII–VIII in furrow and ridge regions, and the description of the arrangement based on the pattern of paragnaths in such regions, are proposed. Further, the terms shield-shaped and pointed (P-bars) bars are redefined, and a new term, crescent-shaped bars, is proposed for paragnaths in the areas VI in some Pseudonereis and Perinereis species. A key for all Pseudonereis species is also included.